2022
DOI: 10.3390/jpm12091432
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Superficial HDR Brachytherapy—Dosimetric Verification of Dose Distribution with Lead Shielding of Critical Organs in the Head and Neck Region

Abstract: Background: Surface brachytherapy, usually characterized by a high dose gradient, allows the dose to be precisely deposited in the irradiated area while protecting critical organs. When the lesion is located in the nasal or ocular region, the organ of vision must be protected. The aim of this study was to verify the dose distributions near critical organs in the head and neck region during a brachytherapy procedure using lead shielding of the eye. Methods: Anthropomorphic phantom using 3D-printing technology w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…With regard to the dose to ocular structures, a recent publication concluded that the decision to use an ocular shielding during facial IRT procedures should be made on a patient-by-patient basis, and based on model-based calculation methods recommended by TG186 [23].…”
Section: Discussionmentioning
confidence: 99%
“…With regard to the dose to ocular structures, a recent publication concluded that the decision to use an ocular shielding during facial IRT procedures should be made on a patient-by-patient basis, and based on model-based calculation methods recommended by TG186 [23].…”
Section: Discussionmentioning
confidence: 99%
“…When considering the clinical relevance of our findings, the main point to highlight is that eyelids are a challenging anatomical location for different reasons. The volume to be treated is established according to a curved spatial arrangement, and TG-186 has proven to be more reliable compared with TG-43, especially in complex volumes [ 22 ]. Another aspect of paramount significance is the strict closeness of CTV to the eye that is a sensitive organ at risk (OAR) to spare.…”
Section: Discussionmentioning
confidence: 99%
“…In the future, using both low and high Z materials for 3D printing, shielded applicators enabling intensity-modulated BT and protection of OARs could be produced. Some dosimetry reports and phantom studies have already been published, but clinical data are lacking [ 39 , 91 , 94 , 95 ]. Larger prospective studies on the efficacy and safety of 3D-printed applicators are also needed before 3D printers come to be a part of our daily clinical practice in a BT department.…”
Section: Discussionmentioning
confidence: 99%
“…In brachytherapy, 3D printing is most often used in gynaecological brachytherapy, followed by superficial brachytherapy for skin cancer and head and neck cancer [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]. Individual reports and small retrospective series have also been published on the use of 3D printing in lung cancer and other thoracic tumours, pancreatic cancer, liver cancer, tumours of the central nervous system, rectal cancer, breast cancer, paediatric tumours, retroperitoneal tumours and others [ 32 , 36 , 41 , 42 , 43 , 44 , 45 , 46 , 47 ].…”
Section: Introductionmentioning
confidence: 99%